2018
DOI: 10.4103/ijmr.ijmr_1295_15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation on sustained virological response in genotype 1/4 chronic hepatitis C treatment-naïve patients from India

Abstract: Background & objectives:The effect of vitamin D supplementation on response to antiviral therapy in hepatitis C virus (HCV) genotype 1 and 4 infection still remains unclear, with studies yielding inconsistent results. The aim of the present study was to assess the effect of vitamin D supplementation on treatment outcome in patients with genotype 1/4 chronic hepatitis C (CHC) infection.Methods:Sixty consecutive, treatment-naïve, genotype 1 and 4 chronic HCV patients were included in the study. The patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Chronic liver inflammation and the subsequent progression to liver cirrhosis and hepatocellular carcinoma (HCC) are typical clinical symptoms of chronic HCV infection. A significant inverse relationship between the severity of inflammatory fibrosis and cirrhosis and serum 25(OH)D 3 levels was observed in HCV patients [32,33,37,40,[62][63][64]. This implies VD deficiency as an independent predictor and risk factor for inflammatory liver complications in HCV patients [38,39,[65][66][67].…”
Section: Effect Of Vd On Hcv Pathogenesismentioning
confidence: 90%
See 1 more Smart Citation
“…Chronic liver inflammation and the subsequent progression to liver cirrhosis and hepatocellular carcinoma (HCC) are typical clinical symptoms of chronic HCV infection. A significant inverse relationship between the severity of inflammatory fibrosis and cirrhosis and serum 25(OH)D 3 levels was observed in HCV patients [32,33,37,40,[62][63][64]. This implies VD deficiency as an independent predictor and risk factor for inflammatory liver complications in HCV patients [38,39,[65][66][67].…”
Section: Effect Of Vd On Hcv Pathogenesismentioning
confidence: 90%
“…Several researchers reported a positive correlation between VD status and sustained virological response (SVR) rates to this standard PEG-IFNα/ribavirin therapy for HCV patients [34,48,51,52,66]. Therefore, VD deficiency was regarded as a potential predictor of an unfavorable response to IFNα-based HCV treatment [45,46,50,64]. In line with this, VD supplementation improved the probability of achieving an SVR following antiviral treatment [37,45,46,49,51,[69][70][71].…”
Section: Effect Of Vd On Hcv Infection Treatment Outcomesmentioning
confidence: 91%
“…20 One of our previous study from Varanasi also revealed the negative association of vitamin D level with stage of fibrosis. 21 The relation of vitamin D with stage of fibrosis could be attributable to anti-inflammatory activity of vitamin D, recruitment of less inflammatory cells leading to less fibrosis. 22 Among the risk factors for HCV acquisition, blood transfusion was the most common occurring in one third of patients followed by IVDU and iatrogenic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials have indicated that vitamin D3 supplementation (1,000 or 2,000 IU/day) is effective for enhancing the efficacy of antiviral treatment with pegylated interferon and ribavirin (PEG-IFN/RBV) in patients with hepatitis C (120-123). Conversely, low serum concentrations of the hormone seem to be related to severe hepatic fibrosis and/or to the lower responsiveness to treatment with PEG-IFN/RBV (124,125).…”
Section: Vitamin Dmentioning
confidence: 99%